THE SOCIAL CHANGE AS THE IMPACT OF GERMAN’S INVASION IN JOHN STEINBECK’S THE MOON IS DOWN (NOBEL: Journal of Literature and Language Teaching, 2014)
he Moon Is Dows is one of John Ernest Steinbeck’s novels. It was published in 1942. Based on this novel, Steinbeck wanted to express his idea about the ambition of the German armies to conquer all Europe. Of course, the invasion creates conflict both to the government and the people of the country being invaded and it has impact to the social change.